Nutrient Sensing and Microbiota Crosstalk: Driving Determinants Shaping Metabolic Stability and Adaptive Physiology for Animal Health - Md. Emran Hossain (International Journal of Molecular Biotechnological Research, 2026)
Nutrient sensing is a fundamental cellular process that enables animals to adapt to fluctuating dietary inputs while maintaining metabolic homeostasis and health. Recent advances reveal that the gut microbiota functions as an active metabolic partner, producing bioactive metabolites that directly influence host nutrient-sensing pathways and downstream cellular responses. This review synthesizes current knowledge on the integration of key signalling networks, including adenosine monophosphate activated protein kinase (AMPK), mechanistic target of rapamycin, and insulin signalling, with microbiota-derived cues such as short-chain fatty acids, bile acid derivatives, and amino acid metabolites. These interactions regulate critical cellular processes, including energy metabolism, immune function, oxidative stress responses, and epithelial integrity. Emerging evidence highlights a dynamic nutrient–microbiota–cell signalling axis that shapes physiological outcomes across multiple tissues. In livestock systems, this integrated framework has profound implications for growth efficiency, reproductive performance, disease resistance, and resilience to environmental stressors. Species-specific differences in microbiome composition and digestive physiology further modulate these responses, emphasizing the need for tailored nutritional strategies. Advances in omics technologies and molecular biotechnology are enabling deeper insights into host–microbiota interactions, facilitating the development of precision nutrition approaches that target specific signalling pathways. Despite significant progress, key mechanistic gaps remain in understanding the spatiotemporal coordination of nutrient sensing and microbial signalling under variable environmental conditions. Future research should prioritize multi-omics integration, longitudinal studies, and translational validation in production settings. Overall, integrating nutrient-sensing biology with microbiome science offers a transformative pathway for optimizing animal health and productivity in a rapidly changing climate.
Keywords: Animal Health; Gut microbiota; cellular signalling; metabolic homeostasis; nutrient sensing pathways